Why co-working spaces in an analogical environment exhibit different recovery abilities under the COVID-19 shock? Evidence from China - Wanyue Wei; Zheng He; Guangming Xiang (Journal of Innovation & Knowledge (JIK), 2024)
Although co-working spaces have attracted significant attention as a type of platform organisation in the sharing economy, little is known about why some spaces faced with an analogical environment demonstrate obvious differences in recovery abilities after sudden shocks, such as the one caused by the COVID-19 pandemic. To understand this novel phenomenon, we collected data from the Chengdu high-tech zone and employed grounded theory and fuzzy set qualitative comparative analysis (fsQCA) to identify the possible causal configurations for high levels of resilience in small and medium-sized platform organisations. Our findings reveal that (1) there are five antecedent configurations that multi-morphologically lead to the same outcome; (2) compared with other antecedent conditions, networking ability and diverse value co-creation with customers play more important roles in the formation of a high level of co-working spaces' resilience; (3) under certain circumstances, a substitutional relationship exists between industrial experience and communication ability; and (4) when the endogenous factors of organisations (e.g. their abilities and resources) coincide with complex external environments, organisational resilience is expressed. In this manner, our study contributes to the organisational resilience literature and research on co-working spaces. Some practical suggestions for the sustainable development of co-working spaces are also provided.
Keywords: L02; M10; O30; 650; Co-working space; Organisational resilience; COVID-19; Value co-creation; Networking ability